Superior neural individuation of mother's than stranger's faces by five months of age. (October 2022) - Peykarjou, Stefanie; Langeloh, Miriam; Baccolo, Elisa; Rossion, Bruno; Pauen, Sabina
Abstract: Human adults are better at recognizing different views of a given face as belonging to the same person when that person is familiar rather than unfamiliar. To clarify the developmental origin of this well-established phenomenon, one group of five-month-olds ( N = 22) was presented with pictures of four different unfamiliar female faces at a fixed rate (6 Hz, 166 msec stimulus onset asynchrony), interrupted every 5th stimulus (1.2 Hz) by either their mother's face (mother oddball condition) or, in different stimulation sequences, a stranger's face (stranger oddball condition). In another group of five-month-olds ( N = 17), stimulation sequences were reversed such that their mothers' or a given stranger's face were repeated at 6 Hz and interrupted every 5 stimuli by pictures of different female faces (mother standard, stranger standard conditions, respectively). Twelve variable images of each identity served as stimulus material. Besides clear frequency-tagged EEG responses at the 6 Hz stimulation rate over the medial occipital region in all conditions, significant activity at 1.2 Hz and harmonics (2.4 Hz, etc.) was observed in this region, reflecting selective responses to facial identity across changes of views. This effect was strongest when the mother's face was immediately repeated at every stimulation cycle (mother standard). Overall, these observations point to an early developmental advantage of identifying a familiar face presented from different views during immediate stimulus repetition.